Investment in agricultural research and development: An account of two-speed growth, underinvestment, and volatility - Stads, Gert-Jan (International Food Policy Research Institute, 2016)
This chapter takes stock of recent agricultural R&D investment in SSA using comprehensive datasets collected under the Agricultural Science and Technology Indicators (ASTI) initiative, facilitated by the International Food Policy Research Institute. The chapter presents an analysis of public agricultural research funding and investment trends in SSA, highlighting important cross-country differences. The discussion also focuses on the main drivers of volatility in agricultural R&D funding over time and suggests a number of policy measures that could mitigate both underinvestment and volatility.